Tools of the New Evangelization of the Church in Poland - Plata, Łukasz (Studia Warmińskie, 2023)
In this article, the author reflected on the tools of the New Evangelization of the Church in Poland. The author first clarified the very concept of the New Evangelization and outlined the terminological differences related to this issue. He went on to point out the external and internal conditions in which the Church in Poland finds itself, and defined the addressees to whom the Gospel message needs to reach. Then, taking into account the facts contained in the article, the author presented the tools of the New Evangelization, which in the dynamically changing reality are used in the Church in Poland.